Studi Status Hara Nitrogen dan Fosfor Pada Endapan Sedimen di Kawasan Bendungan Batujai Lombok Tengah - Sri Mulya Jatiswari; , I Nyoman Soemeinaboedhy; Padusung Padusung (Journal of Soil Quality and Management, 2022)
The Batujai Dam is a reservoir for several river flows in Central Lombok, this makes the Batujai Dam area a trap for sediment and nutrients such as nitrogen and phosphorus. This study aimed to measure the nutrient content of nitrogen and phosphorus in the sediment in the river that enters the Batujai Dam, as well as the impact of irrigation water at the Batujai Dam on agriculture. The method used in this research is descriptive method. Sediment sampling was carried out at each river mouth (Gelondong, Geleger, Ganti, Propok and Selebung). This research was conducted from November 2019 to August 2020. The analysis showed that Gelondong River had a nitrogen content of 0,2661%; Geleger River 0,2258%; Ganti River 0,20765%; Propok River 0,3509%; and Selebung River 0,2972%. The nitrogen content of the Gelondong River, Geleger River, Selebung River and Propok River is included in the medium category, the nitrogen content for Ganti River is low. The results of the phosphorus analysis showed that Gelondong River had a phosphorus content of 103,34 ppm; Geleger River 87,95 ppm; Ganti River 62,72 ppm; the Propok River 50,93 ppm; and the Selebung river 85,32 ppm. The analysis results for phosphorus showed that the phosphorus content of sediment at each location was categorized as very high